Criminal Acts Based on Self-Defense and Forgiveness - Suwinto Johan; Sugiarto (Universitas Medan Area, 2026)
This study examines homicide committed in self-defense. In some cases, victims are treated as offenders after resisting an attack. Establishing self-defense is often difficult due to limited access to evidence and witnesses. The study adopts a normative legal approach supported by primary and secondary sources. The findings indicate that such acts arise from efforts to protect property and other legal interests. In certain cases, the victim uses or seizes a weapon during the incident, leading to harm against the initial aggressor. When sufficient evidence and witness testimony are available, the act may be excused. The study concludes that acts committed in self-defense may be legally justified or excused if supported by credible evidence and testimony. the criminal act of murder can be forgiven if there is a prior criminal act such as theft or rape.